The wear resistance of the layered iron coatings obtained by electrolysis of software / V.V. Artemchuk // Problems of Tribology. – 2012. – № 1. – Р. 72-79. - Артемчук, В.В. (Problems of Tribology, 2014)
The paper presents results of investigations of wear layered electrolytic iron coating. It is shown that the minimum wear of electrolytic iron corresponds to a certain size of mosaic blocks, which is not uniform and depends on the load. Also set reasonable thickness ratio coats, depending on the parameters of their fine structure. It is shown that the layered structure of electrolytic iron coating improves the wear resistance of 1.16 times compared to single layer. Thus, the developed technology of "software" coating improves the mechanical properties of the recovered parts, increase their wear resistance and service life.